Infrared spectroscopy as a rapid tool to detect methylglyoxal and antibacterial activity in Australian honeys. (1st April 2015) - Sultanbawa, Yasmina; Cozzolino, Daniel; Fuller, Steve; Cusack, Andrew; Currie, Margaret; Smyth, Heather
Highlights: A linear relationship found for methylglyoxal(MGO) and bacterial inhibition in honey. Good prediction models using MIR spectral data of honey for both MGO and inhibition. MIR spectroscopy shows promise as a technique to predict bacterial inhibition. Abstract: Methylglyoxal (2-oxopropanal) is a compound known to contribute to the non-peroxide antimicrobial activity of honeys. The feasibility of using infrared spectroscopy as a predictive tool for honey antibacterial activity and methylglyoxal content was assessed. A linear relationship was found between methylglyoxal content (279–1755 mg/kg) in Leptospermum polygalifolium honeys and bacterial inhibition for E scherichia coli ( R 2 = 0.80) and S taphylococcus aureus ( R 2 = 0.64). A good prediction of methylglyoxal ( R 2 0.75) content in honey was achieved using spectroscopic data from the mid infrared (MIR) range in combination with partial least squares regression. These results indicate that robust predictive equations could be developed using MIR for commercial application where the prediction of bacterial inhibition is needed to 'value' honeys with methylglyoxal contents in excess of 200 mg/kg.